Cognitive Behavioral Treatment of Blood-Injection-Injury Phobia: A Case Report - Elif Uzumcu; Sait Uluc (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Blood-injection-injury phobia (BII) is a type of specific phobia that includes intensive anxiety and accompanying avoidance behaviors against medical procedures such as getting blood drawn, vaccination, having an injection and injuries. Unlike other specific phobias, physiological responses (e.g., fainting), called vasovagal syncope, are encountered in blood-injection-injury phobia. Cognitive Behavioral Therapy (CBT) which is based on alleviating avoidance of the feared stimuli through exposure, modifying erroneous beliefs with realistic and adaptive ones in the treatment of blood-injection-injury phobia offers a highly effective approach. In addition to cognitive behavioral techniques, the use of applied muscle tension technique developed to prevent fainting response that may occur during exposure is suggested as an effective method of treating blood-needle-phobia. In this case study, formulation and the cognitive behavioral therapy process including gradual exposure combined with applied muscle tension techniques of a patient, diagnosed as injection phobia, is reported. Behavioral techniques such as applied muscle tension technique and gradual exposure; cognitive restructuring, imagery techniques, psychoeducation and homeworks were used in cognitive behavioral therapy process. After completing 16 sessions of cognitive behavioral therapy, it was observed that the patient started to get blood drawn, to have injections; patients anxiety level and avoidance of medical procedures decreased considerably and she did not experience syncope during medical procedures. As a result, it is thought that the applied muscle tension is a key factor for the efficacy of the exposure steps, and is important to combine it with other cognitive behavioral techniques. [JCBPR 2018; 7(3.000): 144-148]